Flare Gas Recovery System Using Integrated Reciprocating Compressor in Gathering Station C - Tamado Sitorus; Ratnayu Sitaresmi; Hari Hari Oetomo (Penerbitan Universitas Trisakti, 2018)
Flare gas recovery is needed to handling gas flares in oil and gas fields. Field C production wells experience a decline as a result the gas flow pressure in the wellhead becomes low. Low pressure gas enters the LP separator then is burned as a gas flare containing CO2 of 33.38 mol and GHV of 1048.9 BTU / ft3. The flare gas recovery system is applied to reduce gas flares with the integrated reciprocating compressor unit for compression at suction pressure ± 10 psig, discharge pressure ± 100 psig and total flowrate ± 1 MMSCFD. Then the CO2 removal plant produces gas with a CO2 content of 7.09% mol and GHV of 1314.9 BTU / ft3. During operation, requires gas fuel ranging 11 MSCFD and the actual power ranges from 36.46 HP and 39.64 BHP. Economic aspects analysis, gas flare monetization for the period of 2015 until 2022, gross reserves 2,062,917 MMBTU and gross income of US 6,026,744. The operating cost of the the lease purchase scheme, the government US 2,079,696 and the contractor US 1,386,464 with POT 1.7 years and IRR 151.5%.